Reducing Risks and Enhancing Security and Privacy in IoT-based Health Monitoring Application using Blockchain Technology - Chitra, Batumalai; Malathy, Batumalay; Chang, Chelsey, Yin Hang (INTI International University, 2022)
Due to the pandemic Covid-19, human’s health has become one of the most important things to pay more attention to in our daily life. Pandemic Covid-19 could be controlled by social distancing. Therefore, if the condition is allowed, humans are encouraged to not have any physical touching between each other. The Internet of Things (IoT) based Health Monitoring Application is proposed for the medical staff to monitor their patients through their mobile devices. The proposed system allows patients to update their daily health condition to the system and medical staffs are able to monitor their patients through the system by their mobile devices. The proposed system is more feasible than most of the existing system because it is an application that can be accessed from their mobile devices rather than only browsing the website using the laptop or computers. Since patients can update their own health condition to the system, they are not required to go to the hospital for a medical check-up. They are required to go for a medical check-up only if or when doctors find abnormal symptoms in patients’ recorded health. Besides, personal health conditions are considered as confidential information. Therefore, the author would analyze the security risks and the risks of the backend system of the proposed solution. Furthermore, the author would also enhance the security and privacy of the proposed system by implementing Blockchain Technology.